The vertigo years : Europe, 1900-1914 - Blom, Philipp, 1970- (New York : Basic Books, 2008)
Examines how changes from the Industrial Revolution prior to World War I brought about radical transformation in society, changes in education, and massive migration in population that led to one of the bloodiest events in history.
1900 : the dynamo and the virgin -- 1901 : the changing of the guard -- 1902 : Oedipus Rex -- 1903 : a strange luminescence -- 1904 : His Majesty and Mister Morel -- 1905 : in all fury -- 1906 : dreadnought and anxiety -- 1907 : dreams and visions -- 1908 : ladies with rocks -- 1909 : the cult of the fast machine -- 1910 : human nature changed -- 1911 : people's palaces -- 1912 : questions of breeding -- 1913 : Wagner's crime -- 1914 : murder most foul.
Includes bibliographical references (p. 426-452) and index.
Keywords: Europe -- History -- 1871-1918.; Europe -- Civilization -- 20th century; Social change -- Europe -- History -- 20th century; Europe -- Social conditions -- 20th century; Europe -- History -- 1871-1918.